An overview of internationally important plant taxa from Kosovo: An overview of internationally important plant taxa from Kosovo - Millaku, Fadil; Krasniqi, Elez; Berisha, Naim (Hacquetia, 2024)
This study investigates internationally important plant taxa in Kosovo, using data from international lists and local records. The goals are to identify these taxa, outline their significance, provide accessible data for stakeholders, and enhance scientific understanding of their ecology, distribution, and conservation status. The analysis identified 62 internationally significant plant taxa in Kosovo, with the Orchidaceae family prominently represented by 35 taxa. This highlights global conservation concerns for orchids due to their ecological importance and vulnerability to threats like habitat loss and illegal trade. Other important families include Amaryllidaceae, Liliaceae, and Lycopodiaceae. These taxa are listed under frameworks such as the Habitats Directive, CITES, and the Bern Convention, indicating the need for rigorous conservation efforts. Habitat loss and fragmentation are primary threats, impacting 28 taxa, followed by wild collection, grazing, agriculture, urbanization, and tourism. Key habitats include forests, wet grasslands, and alpine grasslands. There are significant discrepancies in the conservation status of these taxa between the European Red List and Kosovo's Red Book, with more taxa classified as threatened in Kosovo. Effective conservation strategies should involve habitat protection, sustainable harvesting, community engagement, and scientific research.